Perubahan Struktur Mikro dan Kekerasan Paduan Co-Cr-Mo-C-N Pada Perlakuan Aging - Kisnandar, Kisnandar; Alfirano, Alfirano; Fitrullah, Muhammad (Program Studi Teknik Metalurgi, Universitas Sultan Ageng Tirtayasa, 2022)
.